The "N" Letter in Arabic: A Phonetic and Semantic Study - Gazi Mutashar Hamza al-Badri, Asst. Prof. (lark, 2023)
this study deals with the [N] letter, phonologically and semantically, being so important in language use. The study s that those who study Arabic need to diversify the linguistic lesson, working with different aspects. The study tackles the [N] letter from different perspectives. Thus, this study presents a different methodology about the [N] letter because it is the most important letter in Arabic due to its allophones and meanings. This is achieved by focusing on the phonological and semantic aspects.